Problematika Profesi Guru dan Solusinya di SMAS Pratama Batangngase - A, Arifuddin; R, Rosdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study was conducted regarding the existence of the phenomenon of low teacher competence. The focus of this research is on the internal and external problematics of teachers in the process of learning to teach . The purpose of this study was to know: 1) the problematics of the teaching profession, 2) the quality improvement efforts of education. The study used a qualitative descriptive research approach. Location of the study: Primary High School. The research subjects were teachers and students. Informants: principals, governance staff and teaching staff . Data collection techniques using the model: observation, and interviews. Test validity of data using triangulation of sources and methods. Data analysis techniques using interactive models consist of data collection, data reduction, data presentation and conclusions. The results of the study show that: 1) Teacher problematics consists of internal problems, including: (a) pedagogical competence, i.e. weak classroom mastery, poor innovation and creativity, low reading interest, lack of mastery of good assessment techniques and teachers lack even not mastery of technology lack of media mastery of learning, professional competence (yes) based (c) personality competence, i.e. a less loving attitude towards the profession. Whereas external problems, include: class size, learning atmosphere, limited facilities and learning resources, disciplines and available libraries.